Metabolome and Transcriptome Reveal Novel Formation Mechanism of Early Mature Trait in Kiwifruit (Actinidia eriantha) - Liao, Guanglian; Liu, Qing; Xu, Xiaobiao; He, Yanqun; Li, Yiqi; Wang, Hailing; Ye, Bin; Huang, Chunhui; Zhong, Min; Jia, Dongfeng (Frontiers in Plant Science, 2021)
Actinidia eriantha is a peculiar berry resource in China, and the maturation period is generally late. Fortunately, we found an early mature A. eriantha germplasm. In order to explore the formation mechanism of its early mature trait, we determined the main carbohydrate and endogenous hormone content of the fruit, and used off-target metabolomics and transcriptomics to identify key regulatory metabolites and genes. We found that early mature germplasm had faster starch conversion rate and higher sucrose, glucose and fructose content when harvested, while, with lower IAA, ABA and ZR content. Through the non-targeted metabolome, 19 and 20 metabolites closely related to fruit maturity and early maturity were identified, respectively. At the same time, WGCNA analysis showed that these metabolites were regulated by 73 and 99 genes, respectively, especially genes related to sugar metabolism were mostly. Based on above, the formation of early mature trait of A. eriantha was mainly due to the sucrose decomposition rate was reduced and the SSC accumulated at low levels of endogenous hormones, so as to reach the harvest standard earlier than the late mature germplasm. Finally, ten SNP loci were developed which can be used for the identification of early mature trait of A. eriantha.